IICA strategy for Jamaica : 2014-2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The IICA Jamaica strategy (IJS) comprises all technical cooperation activities delivered and organized under the four instruments of action (Flagship Projects, Externally Funded Projects, Rapid Response Actions, FonCT) for technical cooperation considered in the 2014-2018 Medium Term Plan. The ICS will respond to requests from the Member States, recognizing the heterogeneity of the hemisphere and the specificities of each region or country, and attempting to reflect the articulation and coordination of IICA’s work at the hemispheric, regional, multinational, and national levels, thereby strengthening the concept of “a Single IICA.